The Utilization of Instagram Social Media as a Promotional and Portfolio Medium: A Media Ecology Perspective - Rozen, AuliyaAsyifa; Hadiyanto (Manunggal Halim Jaya, 2025)
This study explores the use of Instagram as a promotional and portfolio medium by Buka Project Studios through the lens of media ecology theory. The objective of this research is to analyze the content strategies implemented by the Social Media Officer and identify challenges in maintaining visual identity consistency. This study employs a qualitative descriptive approach, with data collected through in-depth interviews with the Social Media Officer and Creative Lead. The findings reveal that Instagram serves as a dynamic digital ecosystem that integrates soft-selling content and portfolio displays to enhance audience engagement and expand professional networks. The research also highlights key challenges in striking a balance between trend adaptation and brand consistency. These findings contribute to the development of media ecology theory in the context of social media marketing, offering practical recommendations for creative industry practitioners to optimize their digital branding strategies.